Assessment of optimum volume of sand mining in an urban river system - Mahmud, Nur Hidayah Huqmah (2018)
The illegal river sand mining activity has taken place in a sand-bed river system in Selangor, Malaysia for decades before legalization was initiated in 2008. The present study focuses on the determination of optimum sand extraction by considering sand during the critical period (dry season). The sand replenishment rate was used as the benchmark in determining the threshold level of the extractable rate in Langat River system, with a specific focus in relating the temporal variation and extraction frequency as the dominant influencing factors. This analysis was executed using Yang equation to predict the sediment replenishment rate. The equation suitability was developed with 43% of similarity by using the discrepancy ratio (ratio of calculated values to measured values) of sediment transport. The sample of sand from different critical locations, flow data, and other physical river parameters were used. Concentrating on sand replenishment rate during the critical period, the optimal sand mining is calculated by reducing 10% from total replenishment rate, which is then converted into Truck Loads per month (taking standard 25 tons truckload). The comparison of sand replenishment rate in high and low flow season proved that the river system has quicker capabilities in sand replenishment rate at the extraction point during the wet season compared to the latter by 83%. Therefore, the quantifiable volume of the extractable sand rate at each extraction points is proposed specifically during dry months (May to September) whereby the slower replenishment rate is critical and riskier.